2014
DOI: 10.1007/s00439-014-1437-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association tests of inversions with application to psoriasis

Abstract: Although inversions have occasionally been found to be associated with disease susceptibility through interrupting a gene or its regulatory region, or by increasing the risk for deleterious secondary rearrangements, no association study has been specifically conducted for risks associated with inversions, mainly because existing approaches to detecting and genotyping inversions do not readily scale to a large number of samples. Based on our recently proposed approach to identifying and genotyping inversions us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…As a consequence, new mutations are not exchanged between the genomic segments of each orientation. The lack of recombination then increases genetic differentiation and leads to characteristic signatures on PCA plots (e.g., De Jong et al, 2012 ; Ma and Amos, 2012 ; Ma et al, 2014 ; Kemppainen et al, 2015 ) such as the ones we observed in some ROIs. Natural selection can also create extended haplotypes.…”
Section: Discussionmentioning
confidence: 67%
“…As a consequence, new mutations are not exchanged between the genomic segments of each orientation. The lack of recombination then increases genetic differentiation and leads to characteristic signatures on PCA plots (e.g., De Jong et al, 2012 ; Ma and Amos, 2012 ; Ma et al, 2014 ; Kemppainen et al, 2015 ) such as the ones we observed in some ROIs. Natural selection can also create extended haplotypes.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, Ma et al . [ 86 ] incorporated the inversions predicted with their principal components analysis-based approach from SNP data [ 43 ] in a GWAS analysis to find association of these regions with psoriasis, a chronic, inflammatory skin disease affecting 2–3% of the world population. They found significant associations of this disease with several candidate inversions, of which only two replicated in two different data sets.…”
Section: Polymorphic Inversions Associated To Phenotypes or Diseasesmentioning
confidence: 99%
“…It turns out that neither of the two candidate inversions overlaps those reported in the InvFEST database [ 39 ]. Therefore, these results should be taken cautiously given that the SNP signatures found might not be owing to an inversion, although the regions detected by the association test may still shed light on the genetic architecture of the disease, as the authors point out [ 86 ].…”
Section: Polymorphic Inversions Associated To Phenotypes or Diseasesmentioning
confidence: 99%
“…In summary, not all PCs identify inversions when confounding factors are present. This will affect methods based purely on cluster structure in PCA projection (e.g., Ma et al (2014); Cáceres and González (2015))); by using association tests and Manhattan plots, our proposed framework is able to distinguish between PCs capturing inversions versus others. This is expected given the role of PCA in population inference and other tasks (Lee et al (2009); Patterson et al (2006); Price et al (2006); Neafsey et al (2010)).…”
Section: Discussionmentioning
confidence: 99%
“…Inversion differences within a population can also appear as clusters in PCA projections (Ma and Amos (2012); Ma et al (2014)), which has motivated computational detection based on characterizing this observed cluster structure (Cáceres and González (2015)). Because not all data induce a clear pattern in PCA projection plots, we were motivated to develop an alternative method based on single-SNP association tests (see Nowling and Emrich (2018c)).…”
Section: Introductionmentioning
confidence: 99%